O gênero relato na valorização da escrita do aluno da EJA - Souza, Márcia Cardoso de (2015)
This research presents the development, analysis and the results of an investigation with genre experience report, through the didactic sequence methodology, and aimed to investigate the impacts of genre experience report on the development of language skills and how it promotes the self-esteem of the students of 2nd year of adult education (high school) of state elementary school and middle in João Pessoa city, Paraíba, in the second semester of the year 2014. Specifically, this study aimed to identify and analyze the main difficulties of these students in the writing of the genre experiences reporting in relation to language skills, propose activities that could instrumentalize them to overcome these difficulties and verify the progress made in producing the report after the interventions developed in modules. From a conception of language as sociodiscursive activity and writing as social practice, our research, qualitative, descriptive and interventional had character and was configured as action research. As a theoretical basis, we adopted the theoretical assumptions of genres, developed by Bakhtin (2011 [1979]) and Bazerman (2007; 2011[2000; 2004]). For the development of didactic sequence in base the proposed Dolz, Schneuwly and Noverraz (2011 [2004]). In this study there are also significant contributions from Antonio Marcuschi (2008), Irandé Antunes (2009), Regina Celi Mendes Pereira (2012), among others. As corpus, present six textual productions of the students involved in the research. In early production, we identify the main difficulties of the students in relation to language skills. After identified the problems, we leave for intervention activities, through the modules, according to the proposal of Dolz , Schneuwly and Noverraz (2011 [2004]). After the intervention process, we found, in the final production of the students who, in general, they managed to overcome the difficulties encountered in the first production in relation to the action capabilities, discursive and linguistic-discursive. Like this, it was established as the literacy activities have expanded the language capabilities overall, while that developed the self-esteem of students.